Glowing Green: A Quantitative Analysis of Photoluminescence in Six North American Bat Species - Briana J. Roberson; Santiago Perea; Daniel DeRose‐Broeckert; Steven B. Castleberry (Ecology and Evolution)
ABSTRACT Photoluminescence produced by excitation with ultraviolet light has been documented in an increasing number of nocturnal–crepuscular mammal species. Here, we provide a quantitative analysis to confirm visual observations of UV‐induced photoluminescence in six North American bat species. We used museum specimens to examine wavelength at peak photoluminescent emission, within and among species. We observed green photoluminescence on the wings, uropatagium, and hind limbs of all 60 museum specimens examined. Spectral scans revealed a consistent emission peak between 520 and 552 nm corresponding to the observed green color. We found no differences in wavelength between species or sexes. Wavelength was not related to specimen age, supporting the use of museum specimens for detection of photoluminescence. Our results suggest the potential for photoluminescence to be homologous in origin among the species we examined. We emphasize the need for further exploration into potential evolutionary and functional roles of photoluminescence across mammalian taxa.